'Window on the West Indies': the photographic imagination of the Society for the Propagation of the Gospel. Issue 1 (2nd January 2018) - Newbury, Darren
Abstract : In the mid-1950s, the Society for the Propagation of the Gospel (SPG) sponsored two substantial photographic exhibitions in Britain, on South Africa and the British West Indies, promoting its mission activities and forming the centrepieces for fundraising campaigns. This article takes the latter exhibition – 'Window on the West Indies' – as an opportunity to examine the Society's evolving approach to the medium, and its photographic archival legacy. Departing from an earlier practice of relying primarily on missionaries to supply photographs from the field, and unlike the somewhat serendipitous circumstances of the South Africa exhibition, 'Window on the West Indies' resulted from a professional commission. In addition to raising issues of ownership and control of photographic production and the photographic image, the commission signalled an increasingly ambitious use of the medium to promote the Society's Christian missionary world view. Yet, I suggest, this very photographic ambition opens the door to alternative readings that escape the limits of the Society's intentions. Beyond its role as mission propaganda, including some highly controlled uses of the photographs within its publicity material, the project can be located in the context of a post-war convergence of international humanist and humanitarian narratives expressed in visual form, and a belief in the capacity of photography as a medium for mutual understanding. Although a Christian future, secured in the act of donation, underpinned the narrative the Society sought to promote through its selective deployment of the photographs, taking a wider view of the collection it is evident that the photographs also speak to a more open, uncertain and imaginative relation to the world depicted. This latter not only draws attention to the specific presence of the photographer but also provides an opening to enable the collection to be refigured for future audiences.